Bilateral Pulmonary Thromboendarterectomy for a Patient with Chronic Pulmonary Thromboembolism Developing Severe Pulmonary Hypertension – A Case Report - Biswas, Prodip K; MA, Gafur; H, Rahman; Dasgupta, Saikat; Chanda, Prasanta K (Cardiovascular Journal, 2022)
Chronic thromboembolic pulmonary hypertension (CTEPH) is a disease with high mortality and few treatment options. Pulmonary thromboendarterectomy (PTE) is the treatment of choice to relieve pulmonary artery obstruction in patients with chronic thromboembolic pulmonary hypertension (CTEPH). This is a challenging procedure in our perspective because of number of regions such as, late diagnosis, scarcity of appropriate instruments, lack of skilled surgeon as it is not familiar to them. Here we are presenting such a case that was also diagnosed incidentally. We successfully operated the patient with chronic pulmonary thromboembolism with severe pulmonary hypertension. Cardiovasc j 2022; 14(2): 176-179